Effect of Ultra-High Pressure on the Extraction of the Free, Esterified, and Bound Phenolics from Dendrobium fimbriatum Hook: Chemical Constituents and Antioxidant Ability - Qinge Su; Junbo Hu; Huimin Cui; Fangyuan Zheng; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Molecules)
This study explores the antioxidant activity and antioxidant mechanism of phenolic compounds (including free (FP), esterified (EP), and bound phenolic (BP)) from Dendrobium fimbriatum Hook (DFH) stems, before and after ultra-high pressure (UHP) treatment. A total of 374 compounds were identified, with 149 showing significant differences in DFH phenolic extracts before and after UHP treatment. UHP treatment significantly increased the total phenolic content (TPC) and total flavonoid content (TFC) and enhanced antioxidant activity in vitro. Particularly, the UEP-DFH, IC50 values in ABTS and DPPH were reduced by 49.6% and 64.1%, respectively. In H2O2-treated HepG2 cells, the extracts demonstrated significant cytoprotective effects, including increased cell viability, ROS reduction, and enhanced GSH levels by 17.8% (UFP-DFH) and 12.5% (UEP-DFH). The activities of GS, GCL, GR, GSH-Px, SOD, CAT, NQO1, and HO-1 were also elevated in UHP-treated extracts. DAPI staining indicated that the extracts promoted nuclear Nrf2 expression, particularly UFP-DFH and UEP-DFH. Molecular docking indicated that vanillic acid could competitively bind to the Keap1-Kelch domain, facilitating activation of the antioxidant pathway. Overall, UHP treatment enhanced both extraction efficiency and antioxidant activity, making it a promising method for improving the bioactivity of DFH in the food and functional food industries.